2021
DOI: 10.3390/ani11040991
|View full text |Cite
|
Sign up to set email alerts
|

Diseases Caused by Amoebae in Fish: An Overview

Abstract: Parasitic and amphizoic amoebae are ubiquitous and can affect a huge variety of hosts, from invertebrates to humans, and fish are not an exception. Most of the relationships between amoebae and fish are based on four different types: ectocommensals, ectoparasites, endocommensals and endoparasites, although the lines between them are not always clear. As ectocommensals, they are located specially on the gills and particularly the amphizoic Neoparamoeba perurans is the most relevant species, being a real pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 101 publications
3
27
0
Order By: Relevance
“…This study identified seven amoeba strains from rainbow trout gills with NGD in Swiss freshwater aquaculture. Amoeba are free‐ranging organisms in water and soil, with the potential to causing disease and death in humans and animals (Padrós & Constenla, 2021). In saltwater salmonids, Neoparamoeba perurans causes AGD and is accompanied by multiple other amoeba species that are far less abundant on the gills than N. perurans (Boerlage et al, 2020; Cano et al, 2019; Crosbie et al, 2012; Dyková & Lom, 2004; English & Lima, 2020; English, Swords, et al, 2019; English, Tyml, et al, 2019; Herrero et al, 2018; Kim et al, 2017; Lima et al, 2017; Marcos‐López & Rodger, 2020; Nowak et al, 2014; Padrós & Constenla, 2021; Taylor et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study identified seven amoeba strains from rainbow trout gills with NGD in Swiss freshwater aquaculture. Amoeba are free‐ranging organisms in water and soil, with the potential to causing disease and death in humans and animals (Padrós & Constenla, 2021). In saltwater salmonids, Neoparamoeba perurans causes AGD and is accompanied by multiple other amoeba species that are far less abundant on the gills than N. perurans (Boerlage et al, 2020; Cano et al, 2019; Crosbie et al, 2012; Dyková & Lom, 2004; English & Lima, 2020; English, Swords, et al, 2019; English, Tyml, et al, 2019; Herrero et al, 2018; Kim et al, 2017; Lima et al, 2017; Marcos‐López & Rodger, 2020; Nowak et al, 2014; Padrós & Constenla, 2021; Taylor et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The analogous disease in freshwater fish is NGD. However, the causative agent of NGD remains unclear (Padrós & Constenla, 2021) and a multi‐amoeba and multifactorial aetiology has also been suggested (Dykova & Tyml, 2016). Several amoeba species have been described in NGD‐affected fish farmed in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fish gills are easily accessible to surrounding pathogens (Pratte et al 2018). Irritation of the gills caused by infection with pathogens can cause respiratory failure and osmoregulatory complications in fish (Padrós and Constenla 2021). The anatomy of fish gills includes the arch of the gills, primary lamellae, and secondary lamellae, which are perpendicularly arranged with primary lamellae.…”
Section: Histological Observation Of Amoeba In the Gill Oreochromis Spmentioning
confidence: 99%
“…Other abundant pathogenic genera, such as Paramoeba and Hartmanella, including harmful amoeba species, were detected in the sediment and water column. These species have been associated with NGD in freshwater fish and with Amoebic Gill Disease (AGD) in other species, such as Atlantic salmon (Salmo salar), rainbow trout (Oncorhynchus mykiss), brown trout (Salmo trutta) or turbot (Scophthalmus maximus) (150). Moreover, although Nolandella, the most abundant amoeba genus in our study, does not seem to be pathogenic, it has been reported to colonize the gills of farmed Atlantic salmon with AGD (151).…”
Section: Discussionmentioning
confidence: 55%